Cultural and religious attitude to banking in the great world religions - Kurkliński, Lech (Annales. Etyka w Życiu Gospodarczym, 2019)
The article examines the attitude of the great world religions (Judaism, Christianity, Islam, Buddhism, Hinduism, and Confucianism) toward the world of finance, including banking. The issue of usury plays a key role in the evolution of ethical aspects related to obtaining compensation for money lending. The presented analysis also focuses on other aspects of banking activities, such as saving, investing and the institutional development of the banking sector. The author underlines the far-reaching convergence between the religions in this area, in spite of the considerable variation in historical and geographical conditions of their formation. The importance of cultural (religious) differences, including some fundamental nuances that affect the banking management in different regions. For successful development, large multinational corporations have to take into consideration the above-mentioned circumstances, regardless of the globalisation processes.